Role of LOTR1 in nutrient transport through organization of spatial distribution of root endodermal barriers - Li, Baohai; Kamiya, Takehiro; Kalmbach, Lothar; Yamagami, Mutsumi; Yamaguchi, Katsushi; Shigenobu, Shuji; Sawa, Shinichiro; Danku, John M.C.; Salt, David E.; Geldner, Niko; Fujiwara, Toru (Elsevier, 2017)
The formation of Casparian strips and suberin lamellae at the endodermis limits the free diffusion of nutrients and harmful substances via the apoplastic space between the soil solution and the stele in roots [1–3]. Casparian strips are ring-like lignin polymers deposited in the middle of anticlinal cellwalls between endodermal cells and fill the gap between them [4–6]. Suberin lamellae are glycerolipid polymers covering the endodermal cells and likely function as a barrier to limit transmembrane movement of apoplastic solutes into the endodermal cells [7, 8].However, the current knowledge on the formation of these two distinct endodermal barriers and their regulatory role in nutrient transport is still limited. Here, we identify an uncharacterized gene,LOTR1, essential for Casparian strip formation in Arabidopsis thaliana. The lotr1 mutants display altered localization of CASP1, an essential protein for Casparian strip formation [9], disrupted Casparian strips, ectopic suberization of endodermal cells, and low accumulation of shoot calcium (Ca). Degradation by expression of a suberin-degrading enzyme in the mutants revealed that the ectopic suberization at the endodermal cells limits Ca transport through the transmembrane pathway, thereby causing reduced Ca delivery to the shoot. Moreover, analysis of the mutants showed that suberin lamellae function as an apoplastic diffusion barrier to the stele at sites of lateral root emergence where Casparian strips are disrupted. Our findings suggest that the transmembrane pathway through unsuberized endodermal cells, rather than the sites of lateral root emergence,mediates the transport of apoplastic substances such as Ca into the xylem.